Development of Multi-Physics Workflow for the Analysis of Superconductive Cables Subject to Nuclear Heating - Casciello, Martina; Riva, Nicolo; Placido, Daniele; Hartwig, Zach; Segantin, Stefano; Savoldi, Laura (IEEE transactions on applied superconductivity, 2025)
High Temperature Superconductor (HTS) magnets, wound using cable-in-conduit, can support the development of compact, nuclear fusion machines, provided they can be kept at the appropriate temperature and shielded from the damage of nuclear irradiation. A comprehensive interdisciplinary integrated multi-physics approach is essential to address thermal, mechanical, and cryogenic aspects, and is addressed in this paper. The first step of the proposed workflow is to internally generate simplified and consistent CAD from the central spline of the HTS stacks or conductors. This simplification applies to both the cables and the plates of the magnets, resulting in a design that is easy to use for neutronic simulations. Open-source software, such as FreeCAD, is employed for this purpose. Subsequently, the generated CAD are imported into OpenMC, an open-source Monte Carlo code capable of evaluating neutronic flux in 3D geometries. The magnets undergo simulation with a point source representing the plasma, and the resulting heat is non-uniformly distributed on the magnets and lumped in a power density profile along the curvilinear coordinate of the conductor axis. Based on the same layout, the magnetic (self) field profile is assessed using COMSOL software, and used as input to the 1D thermal-hydraulic analysis, which is carried out using OPENSC2. The workflow is shown to be applicable to both planar tokamak coils and non-planar 3D stellarator superconducting coils, offering a significant versatility.